Investigations concerning fast surface states of semiconductors by means of acoustic methods - OPILSKI, Aleksander; PUSTELNY, Tadeusz (Archives of Acoustics, 1989)
The paper deals with the results of investigations an n-Si surfaces, obtained by determining acoustically the parameters of fast surface states in semiconductors. This new method is theoretically based on the analyses of the influence of surface states in a semiconductor on the propagation of a Rayleigh surface wave in a layer system of piezoelectric and semiconducting layers. It is possible to determine the effective life time τ of the charge carrier of fast surface states, as well as the velocity of recombination, g, of the carriers in these states.